Performance evaluation: analysis of the autonomous service of tax administration at Lara (SAATEL) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2014)
The work is aimed at developing leading to improved process performance evaluation of staff of the Autonomous Service of Tax Administration Lara (SAATEL). The study is part of a non-experimental, cross leaning against a descriptive field research design. The population is thirty-nine (39) attached SAATEL subjects. To collect observation data were used; The semi-structured interview, a questionnaire with Likert scale and an array of SWOT analysis. For the analysis and interpretation of data characteristic of the descriptive statistics techniques were used. He conducted the research process was concluded that one traditional formal system of performance evaluation to assess employees, there are also problems supervision, integration of the worker in the organization or position held and underutilization of staff potential and / or poor motivation, on the other hand, it was established that there was a need to develop a body of guidelines for the institution to identify subjects that require improvement in certain areas of activity and select those conditions promoting or transfers
Keywords: performance evaluation; strategic guidelines; autonomous tax administration service of Lara state